On the occasion of the 90th birthday of Leonid Antonovich Serafimov - A. K. Frolkova (Тонкие химические технологии, 2019)
The article is dedicated to the 90th birthday of Leonid Antonovich Serafimov, an outstanding scientist, Doctor of Engineering Sciences, professor at the M.V. Lomonosov Moscow State University of Fine Chemical Technologies. Serafimov made an invaluable contribution to the development of the theoretical foundations of chemical technology. The article briefly describes the research conducted by the scientific school "Theoretical Foundations and Technological Principles of Mass-Transfer and Combined Processes of Organic Synthesis" founded and led by him. Special attention is given to the ideological component of his scientific and pedagogical activity; and his active civil position, encyclopedic knowledge and remarkable personal qualities are also duly noted.